Penipuan Online sebagai Bentuk Kejahatan Siber dalam Perspektif Kriminologi - Anisa Sahara; Kuswandi Kuswandi (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This study analyzes online fraud as one of the most common forms of cybercrime in Indonesia, which has expanded alongside rapid advances in information and communication technology. These crimes utilize digital platforms such as social media, online marketplaces, and fraudulent websites to deceive victims for unlawful financial gain. The research aims to examine online fraud from a criminological perspective by identifying its causes, patterns, and relevance to routine activity theory and differential association theory. A normative juridical method is employed, using statutory, conceptual, and case-based approaches, with qualitative and descriptive analysis. The findings show that online fraud reflects a shift from conventional fraud to digital-based crimes, driven by low public awareness of cybersecurity, easy access to technology, and weak online supervision. Several fraud schemes were identified, including online investment scams, phishing, and identity impersonation. This study highlights the need for an integrated approach that goes beyond law enforcement by emphasizing digital literacy, public education, and cross-sector collaboration to reduce cybercrime in Indonesia.